Implementation of Professional Competency Development for Teachers in Islamic Religious Education - Vita Lastriana Candrawati; Zikry Septoyadi; Dulyawit Naknawa; Abdul Karim Ali; Adil Ahmad Fauzi (Institut Agama Islam Negeri Palopo, 2026)
Teaching and learning activities at MTsS Maghfirah Islamic Leadership Boarding School (MILBoS) have generally been running well, but still require strengthening and development in several aspects, particularly in improving teacher competency as the main factor determining the quality of learning. Based on Law Number 14 of 2005 concerning Teachers and Lecturers, Article 8, teacher competency includes pedagogical, personality, social, and professional competencies obtained through professional education. Therefore, developing teacher competency in Islamic religious education is a strategic need in improving the quality of education, especially in the context of boarding schools that have the characteristics of integrated academic and religious development. This study aims to describe and analyze the implementation of teacher competency development at MTsS MILBoS. The study used a qualitative method with a descriptive-analytical approach. This approach produces descriptive data in the form of written and spoken words from informants, as well as behavior observed in natural contexts, rather than quantitative data. Research informants consisted of the principal, teachers, and students who provided information related to the implementation of the teacher competency development program in Islamic religious education. In addition to primary data, this study also utilized relevant secondary data. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out in three stages: data reduction, data presentation, and drawing conclusions and verification using an interactive analysis model. The results of the study indicate that the implementation of teacher competency development at MTsS MILBoS was effective and had a positive impact. Teachers showed high enthusiasm in planning and implementing various development programs, resulting in significant improvements in pedagogical, social, personality, and professional competencies. Thus, teacher competency development in Islamic religious education at MTsS MILBoS contributed to improving the quality of learning and strengthening the quality of education in the boarding school environment.